Tetrahedral μ4-chloride and in situ generated octahedral μ6-sulfide templating Co8 complexes with different distortions of the cube. Issue 30 (17th March 2020) - Yu, You-Zhu; Guo, Yu-Hua; Zhang, Yan-Ru; Tian, Xiu-Juan; Zhang, Xian-Ming
Abstract : Two unprecedented octanuclear Co8 clusters with distorted cubes were synthesized using chloride and in situ generated sulfide as templates, in which strong intra-cluster antiferromagnetic interactions were found. Abstract : Herein two unprecedented octanuclear Co8 clusters are presented, [Cl@Co8 (TEOA)4 (CH3 CN)Cl3 ] (1) and [S@Co8 (DEOA)6 (NCS)2 ] (2) (H3 TEOA = triethanolamine, H2 DEOA = diethanolamine), in which tetrahedral μ4 -chloride and in situ generated octahedral μ6 -sulfide are used as templates. In spite of them being derivatives of cubes, eight Co atoms in 1 consist of two co-centered tetrahedra of different sizes, whereas in 2 they appear as a rhombohedron formed via elongating a cube along the C 3 -axis direction. Strong intra-cluster antiferromagnetic interactions were found.